Relevance Analysis of Akad Ijarah Muntahiyah Bittamlik at BMT Syariah Bening Suci Prambanan with Fatwa of DSN MUI No. 27/DSN-MUI/III/2002 - Rifqi Firmansyah; Muh Nashirudin (Universitas 17 Agustus 1945 Surabaya, 2023)
The growing Ijarah contract has resulted in this Ijarah contract being changed to the Ijarah Muntakiyah Bittamlik contract, which is a lease that ends with the use of property. In fact, Islamic banks rarely use IMBT, although in the interest of diversifying cost products , the following arrangements are considered mandatory in order to streamline their implementation. The following research uses a type of field research that is analytical descriptive in nature . As well as with the completeness of library research and content analysis by carrying out a comparison of the MUI Akad fatwa regulations with the practices contained in the BMT Syariah Bening Suci Prambanan. The results of the following research are that the Ijarah Muntakiya Bittamlik MUI contract and the practice of Ijarah Muntakiya Bittamlik BMT Syariah Bening Suci Prambanan are appropriate. Its application includes Fatwa No.09/DSN-MUI/IV/2000 concerning Ijarah Financing, No.71/DSN-MUI/VI/2008 concerning Sale and Purchase, No.27/DSN-MUI/III/2002 concerning al-Ijarah al- Muntakiya Bittamlik, No.56/DSN-MUI/V/2007 regarding Revision of Ujrah in LKS, No.89/DSN-MUI/XII/2013 concerning Sharia Refinancing.